What is the Value of an Existing Forest Stand? - Andres Susaeta; Chris Demers (EDIS)
Traditionally, the land expectation value (LEV) formula, the present value of perpetual cash inflows of timber revenues minus the present value of cash outflows of costs, has been employed as the main indicator of the value of a forest investment. However, when a forest stand is already established, the LEV approach is incomplete because it applies only to bare land. Thus, it is necessary to determine the value of a property with an existing forest stand. This 3-page fact sheet written by Andres Susaeta and Chris Demers and published by the UF/IFAS School of Forest Resources and Conservation provides the formula to determine the value of an already established forest stand at any stage of its development. This approach, known as the forest value formula, includes the value of the timber and the land. It can be used to compare the value of the stand when it is immediately harvested or when it is economically immature. http://edis.ifas.ufl.edu/fr423